The Relationship Between Dominance and Cyber Dating Abuse in Dating as Early Adults - Mega Asri Meilina; Amri Hana Muhammad (Journal of Social and Industrial Psychology, 2024)
Technology has various applications, including communication with partners. However, cyber dating abuse can negatively impact relationships. This behavior victimizes partners through online media and can stem from dominance in the relationship. Early adulthood is a time when individuals begin to engage in more intimate romantic relationships, which may increase the risk of cyber dating abuse. This correlational quantitative study aims to determine the relationship between dominance and cyber dating abuse in early adults who are dating. The sample consisted of 255 early adults who are dating and was selected using accidental sampling. The study employed the dominance and cyber dating abuse scale instruments for data collection, each comprising of 27 valid items. The reliability coefficient values for the dominance and cyber dating abuse scales were 0.913 and 0.970, respectively. The data was analyzed using Spearman Rho with a significance value (p) of 0.000 and a correlation coefficient (r) of 0.709. The analysis results indicate that dominance falls within the moderate category, while cyber dating abuse falls within the low category. Therefore, we can conclude that the hypothesis stating “There is a relationship between dominance and cyber dating abuse in early adults who are dating” is accepted. In other words, the higher the dominance in the relationship, the higher the cyber dating abuse in early adults who are dating, and vice versa